2020
DOI: 10.1016/j.celrep.2020.107701
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Reprogramming of Cancer-Associated Fibroblasts Deregulates Glucose Metabolism and Facilitates Progression of Breast Cancer

Abstract: Highlights d Pro-glycolytic CAFs fuel cancer cell metabolism to support breast tumor growth d CAFs attain a pro-glycolytic phenotype by epigenetic control of glycolysis d Chronic hypoxia enables epigenetic reprogramming of glycolysis in fibroblasts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
143
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(144 citation statements)
references
References 70 publications
1
143
0
Order By: Relevance
“…It results in a decrease in lactate secretion and aerobic glycolysis. It was recently shown that extinction of PDK in αSMA+ fibroblasts co-injected with 4T1 cells in an orthotopic tumors model decreases tumor growth [ 77 ]. In the same study, the authors show that breast cancer derived human CAFs are pro-glycolytic compared to fibroblasts from benign lesions.…”
Section: Targeting Mitochondria To Counteract Caf-cancer Cells Symmentioning
confidence: 99%
“…It results in a decrease in lactate secretion and aerobic glycolysis. It was recently shown that extinction of PDK in αSMA+ fibroblasts co-injected with 4T1 cells in an orthotopic tumors model decreases tumor growth [ 77 ]. In the same study, the authors show that breast cancer derived human CAFs are pro-glycolytic compared to fibroblasts from benign lesions.…”
Section: Targeting Mitochondria To Counteract Caf-cancer Cells Symmentioning
confidence: 99%
“…In prostate cancer, TGF-β derived from cancer cells activates fibroblasts via NADPH oxidase 4-mediated reactive oxygen species signaling [ 16 ]. Hypoxia causes the epigenetic reprogramming of breast fibroblasts, resulting in them gaining CAF-like pro-glycolytic phenotypes [ 17 ]. In addition, numerous miRNAs have been reported to be involved in the differentiation of normal fibroblasts into CAFs [ 18 ].…”
Section: Cancer-associated Fibroblasts (Cafs)mentioning
confidence: 99%
“…CAFs, as other fibroblasts, possess spindle-shaped morphology (Figure 1), although gained increased proliferation rates [1]. CAFs are extensively described in literature, including [1,[7][8][9][10][12][13][14][15][16][17]. In particular, CAFs can be defined as a heterogenous population of connective tissue cells that contribute to cancer progression by secreting specific molecules, including growth factors, proteases, chemokines and cytokines.…”
Section: Cancer-associated Fibroblasts Tumor Microenvironment and Ramentioning
confidence: 99%
“…CAFs, which is the predominant cell type present in the tumor stroma, are involved in angiogenesis by secreting various pro-and antiangiogenic factors [74]. CAFs adapt to local hypoxia by changing metabolism and increasing, for example, glycolysis, catabolic activity, autophagy, as well as enhancing the VEGF signaling [1,17,[74][75][76]. For instance, CAFs were reported to deregulate glucose metabolism following epigenetic reprogramming and thus facilitating the progression of breast cancer [17].…”
Section: Hypoxia and Cafsmentioning
confidence: 99%